2004
DOI: 10.1302/0301-620x.86b2.14341
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite-coated, cementless total knee replacement in patients aged 75 years and over

Abstract: We have carried out a prospective study comparing the results at five years in patients older than 75 years of age undergoing hydroxyapatite-coated, cementless total knee replacement (TKR) with those who were younger. The Knee Society clinical rating scores were recorded before and after operation. Of 559 patients undergoing TKR, 135 were in the elderly age group. The knee scores at five years or more showed comparable results, with patients under 75 years of age reaching a score of 183 and those aged 75 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…This prosthesis has been previously shown to produce similar results in patients over the age of 75 years when compared with those younger patients. 20 Function after surgery has already been reported, with a number of Survival curve using revision as an end-point.…”
Section: Discussionmentioning
confidence: 99%
“…This prosthesis has been previously shown to produce similar results in patients over the age of 75 years when compared with those younger patients. 20 Function after surgery has already been reported, with a number of Survival curve using revision as an end-point.…”
Section: Discussionmentioning
confidence: 99%
“…3 Survival analyses alone do not accurately reflect the true clinical outcome. 8 Several other studies have concluded that a good outcome can be anticipated following replacement in both younger [4][5][6]11,21 and older patient cohorts, 7,9,10,12,13,22 as defined by objective clinical outcome measures. However, there are a number of limitations to these studies.…”
Section: Discussionmentioning
confidence: 99%
“…8 Objective clinical measures suggest that functional improvements are less impressive in the elderly, but the overall outcome is comparable across all ages. 4,[9][10][11][12][13] Objective clinical measures are increasingly considered less representative of the outcome from the patient's perspective. 14 As a result, growing emphasis is now placed on PROMs to define success following joint replacement surgery in England.…”
mentioning
confidence: 99%
“…31 Cross and Parish 32 described outcomes in 1000 patients with very satisfactory results with a mean total KSS of 180 and survival of 99.14% (95% CI 92.5 to 99.8) at ten years. The favourable long-term survivorship of this TKR further supports the use of HA-coating of uncemented implants.…”
Section: Discussionmentioning
confidence: 99%